Toward a Speculative Pedagogy - Carstens, Delphi (Critical Studies in Teaching and Learning, 2023)
In resistance to capitalist logics of speculation, this article argues for audacious pedagogies of speculative fabulation. The kinds of pedagogical endeavours that times of uncertainty call for are by no means straightforward, calling as I argue along with Elizabeth de Freitas (2020) writing in this issue, for more venturesome approaches informed by speculative posthuman inquiries and exploratory new materialisms. The Anthropocene or Capitalocene are terms that capture equivocal nature of the crisis-riven present. Laden with contradiction and destruction, these descriptors also embody strange afterlives. Beyond problematic present/futures produced by humans only for themselves lie intimate and uncanny sympoiesis, world-buildings and meaningmakings with non-human others and more than human processes. In accounting for these as well as for the already entangled material conditions of our time, pedagogy needs to pay attention to the slippery nature of cognition itself; a task to which the genre of science-fiction or speculative fabulation (SF) is primed.